Indian environmental law :Key concepts and principles - Shibani Ghosh,Ed (Orient Blackswan, 2019)
for more than three decades now, the Indian Courts have delivered far-reaching judgments on a range of significant environmental matters. In their effort to adjudicate complex disputes with serious environmental repercussions, involving the interplay of multiple social, economic and political factors, the Courts have developed a framework of environmental rights and legal principles, which now forms an integral part of Indian environmental jurisprudence. The judiciary invokes this framework creatively to identify constitutional, statutory and common Law obligations of public and private actors to protect the environment, and to enforce the performance of related duties. There is, however, limited in-depth study of these crucial rights and principles in existing legal literature.